POSTER BY VIKTOR PETROVYCH BYSTRYAKOV (1943–2021) - Буднік, А. В.; Купрієнко, Є. М.; Пилипенко, І. Я. (Art and Design, 2023)
Purpose: research of the little-studied and unanalyzed poster heritage of the Ukrainian artist Viktor Petrovych Bystryakov (1943–2021). Methodology. The method of art analysis, comparative and historical methods is applied. Results. The poster work of the famous Ukrainian artist Viktor Bystryakov was studied. It was found that during about 40 years, Viktor Petrovich Bystryakov created more than 4 dozen poster works, which were introduced into scientific circulation only partially and tendentially, under the ideological order of the corresponding social system. It was found that the total number of printed posters authored by Viktor Bystryakov, which are in the archives of the Vernadsky National Library of Ukraine, amounts to 813,280 copies and thus cannot be ignored by the art science. It was found that despite the political engagement of poster practices of the era of late socialism in the 1970-80s, there was a possibility of artistic escapism through work with the genres of spectacular or cultural posters, as a less ideologically controlled environment. It has been established that one of the representatives of such "quiet" opposition can be considered the famous Kyiv artist Viktor Petrovich Bystryakov, who, starting from his studies at the Kyiv State Art Institute, turned to general civilizational or purely artistic themes. Scientific novelty. For the first time, the artistic regularities and technical possibilities of the implementation of metaphorical poster solutions of the artist V. Bystryakov were characterized through the publication of a little-known volume of his works. The practical significance lies in the possibility of analyzing formal design techniques when creating posters for the purpose of their use in design education.